Dissociable Effects of Lesions to Orbitofrontal Cortex Subregions on Impulsive Choice in the Rat - Mar, Adam C. (Society for Neuroscience, 2011)
The orbitofrontal cortex (OFC) is implicated in a variety of adaptive decision-making processes. Human studies suggest that there is a functional dissociation between medial and lateral OFC (mOFC and lOFC, respectively) subregions when performing certain choice procedures. However, little work has examined the functional consequences of manipulations of OFC subregions on decision making in rodents. In the present experiments, impulsive choice was assessed by evaluating intolerance to delayed, but economically optimal, reward options using a delay-discounting paradigm. Following initial delay-discounting training, rats received bilateral neurotoxic or sham lesions targeting whole OFC (wOFC) or restricted to either mOFC or lOFC subregions. A transient flattening of delay-discounting curves was observed in wOFC-lesioned animals relative to shams—differences that disappeared with further training. Stable, dissociable effects were found when lesions were restricted to OFC subregions; mOFC-lesioned rats showed increased, whereas lOFC-lesioned rats showed decreased, preference for the larger-delayed reward relative to sham-controls—a pattern that remained significant during retraining after all delays were removed. When locations of levers leading to small–immediate versus large–delayed rewards were reversed, wOFC- and lOFC-lesioned rats showed retarded, whereas mOFC-lesioned rats showed accelerated, trajectories for reversal of lever preference. These results provide the first direct evidence for dissociable functional roles of the mOFC and lOFC for impulsive choice in rodents. The findings are consistent with recent human functional imaging studies and suggest that functions of mOFC and lOFC subregions may be evolutionarily conserved and contribute differentially to decision-making processes.